Vertical Transmission of Group B Streptococcus, Prevalence, Associated Factors, and Antimicrobial Susceptibility Profile among Newborns Delivered at Health Facilities in Jigjiga City, Ethiopia - Addisu Tesfaye; Mahlet Fekede; Fasil Getu; Surafel Mekuria; Tigist Abebe; Daniel Tollosa; Shamil Barsenga; Bawlah Tahir; Abdurahman Kedir Roble; Sara Tesfaye; Muluken Walle (International Journal of Microbiology)
Background. Group B Streptococcus (GBS) colonizes the rectovaginal area of women and vertically transmitted to neonates. This bacterium has been linked to severe neonatal complications including pneumonia, septicemia, and meningitis. GBS shows an increased resistance to commonly used antibiotics. Thus, we assessed the vertical transmission, contributing factors, and antimicrobial resistance patterns of GBS among newborns delivered at selected Hospitals in Jigjiga City. Methods. Hospital-based cross-sectional study was conducted from 1st June 2022 to 30th April 2023. A total of 849 pregnant women admitted to delivery wards from two hospitals were screened for GBS colonization. Subsequently, 162 GBS-colonized pregnant women and their newborn babies were included. A semistructured questionnaire and a review of medical records were used to collect the sociodemographic and clinical characteristics of the study participants. Trained nurses collected swab samples from the vaginal-rectal area of pregnant women and the nasal, ear canal, and umbilical areas of newborn babies. Samples were inoculated on Todd Hewitt broth media supplemented with gentamycin and nalidixic acid and then subcultured on blood agar. Colony characteristics, Gram stain, and catalase test were used for identification. All gram-positive cocci, B-hemolytic, and catalase-negative isolates were further identified using Christie–Atkins–Munch–Petersen and a bacitracin test. The modified Kirby-Bauer disk diffusion method was used for antimicrobial susceptibility testing. Data were analyzed using SPSS version 26. Logistic regression analysis was used to determine the factors associated with vertical transmission of GBS, and statistical significance was set at p values <0.05. Result. The overall vertical transmission rate was 41.4% (67/162). History of preterm labor (Adjusted odds ratio (AOR) = 2.25; 95% CI: 1.11, 4.59), history of urinary tract infection (UTI) at current pregnancy (AOR = 2.25; 95% CI: 1.11, 4.59), and prolonged rupture of membranes greater than 18 hours (AOR = 2.23; 95% CI: 1.13, 4.4) were significantly associated with vertical transmission of GBS from previously colonized mothers to their newborn babies. Regarding GBS antibiotic susceptibility profile, a significant degree of resistance was observed to penicillin (29.9%), tetracycline (22.4%), ampicillin (20.9%), and clindamycin (19.4%). Conclusion. Our study documented a high prevalence of vertical transmission rate of GBS from pregnant women to their babies, with an overall transmission rate of 41.4%. The study identified the presence of antimicrobial-resistant GBS to penicillin, ampicillin, clindamycin, ciprofloxacin, and chloramphenicol. The organism was susceptible to vancomycin, followed by azithromycin, ceftriaxone, and erythromycin. Our study also reported MDR at 13.4%. Based on our findings, there is a need for antenatal culture-based GBS screening, maternal vaccination, and large-scale epidemiological and serotype identification studies to be put into practice in the study area.